Cultural competence in dementia care: Care workers and managers perspectives on physical and social environments in Long-Term Care - Lisa Spang; Katarina Baudin (PLoS ONE, 2026)
This study explores how cultural identity can be preserved in dementia long-term care as resident populations become increasingly diverse. Using a deductive approach informed by the Person–Environment fit framework, the study examines care workers’ and managers’ experiences and strategies across physical and social environments. Findings show that indoor and outdoor settings, communication practices, activities, relationships, and cultural rituals all influence culturally responsive care. Competing priorities such as safety, limited resources, and varying cultural competence, shape the long-term resident’s wellbeing, environment and everyday life. The study highlights the need for interpretation services, structured cultural competence training, and sensory-based approaches to enhance residents’ well-being and inclusion.